Student’s Digital Intentions Prediction Using CatBoost - Zulwisli; Ambiyar; Muhammad Anwar; Andhika Herayono (Jurnal Teknologi Pendidikan)
Digital Entrepreneurship (DE) represents a new paradigm in entrepreneurship that leverages digital technology to create, manage, and expand businesses. By integrating advanced digital tools and platforms, DE plays a crucial role in reshaping traditional business models, driving innovation faster, and enabling enterprises to reach broader markets. Moreover, digital technologies enhance customer interaction, allowing companies to provide personalized experiences that cater to consumer needs. This transformative approach benefits individual entrepreneurs and contributes to broader economic development. One of DE’s most significant impacts is its ability to foster economic growth. By embracing digital entrepreneurship, businesses can create new jobs, increase competitiveness, and adapt more effectively to the demands of the digital age. These factors collectively ensure that economies are better positioned to thrive in a technology-driven world. A recent study developed a predictive model using the CatBoost algorithm to understand better the factors influencing digital entrepreneurship. This advanced machine learning method was applied to data collected from thousands of college students, encompassing various demographic, psychological, and business-related variables. The results demonstrated the model’s high accuracy in predicting intentions toward digital entrepreneurship, offering a reliable framework for analysis and application. The study identified three key factors influencing students’ intentions to pursue digital entrepreneurship. These are digital skills, which reflect their ability to navigate and utilize digital tools effectively; self-efficacy, their confidence in their entrepreneurial capabilities; and entrepreneurship education, which equips them with the knowledge and skills needed to innovate and create businesses. These findings provide valuable insights for educational institutions and policymakers. By emphasizing digital skills training, fostering self-efficacy, and enhancing entrepreneurship education programs, they can better prepare students to succeed in the digital economy. Such targeted initiatives empower individuals and contribute to the sustainable growth of digital entrepreneurship, reinforcing its role as a driver of innovation and economic progress.